Synoptic weather types that have caused heavy precipitation in Estonia in the period 1961–2005 - Mätlik, O; Post, P (Estonian journal of engineering, 2008)
The subjects of the study are heavy precipitation and weather types, caused by it, in Estonia in the period 1961-2005. Precipitation is labeled 'heavy rainfall' when its 24-hour accumulated sum is at least 50 mm. The work was concentrated on manual analysis and classification of synoptic situations as well as on the definition of tracks of cyclones, fronts and troughs in order to better understand the circumstances leading to the heavy rainfalls. Most of heavy rainfalls have been caused by the passage of different depressions and frontal systems. The role played by convective precipitation is less significant. Most frequently, heavy rainfall is brought to Estonia by the southern cyclones, born in the region of the Black Sea or the Mediterranean Sea.